2013
DOI: 10.1155/2013/208912
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a Rodent Hindlimb Model of Secondary Lymphedema: Surgical Radicality versus Radiotherapeutic Ablation

Abstract: Secondary lymphedema is an intractable disease mainly caused by damage of the lymphatic system during surgery, yet studies are limited by the lack of suitable animal models. The purpose of this study was to create an improved model of secondary lymphedema in the hindlimbs of rodents with sustained effects and able to mimic human lymphedema. This was achieved by combining previously reported surgical methods and radiation to induce chronic lymphedema. Despite more radical surgical destruction of superficial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…These edematous changes have been reported previously 2 , 25 , 26 . The circumference of the hindlimb and the volume and stasis of lymph fluid were measured in order to evaluate the extent of lymph edema 20 , 27 , 28 . These parameters all increased in edematous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These edematous changes have been reported previously 2 , 25 , 26 . The circumference of the hindlimb and the volume and stasis of lymph fluid were measured in order to evaluate the extent of lymph edema 20 , 27 , 28 . These parameters all increased in edematous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches use conventional techniques to estimate the rodent hindlimb volume when reporting outcomes of experimental lymphedema treatment. Common parameters are the assessment of water displacement 36 , circumferential length 37 38 39 or paw thickness 7 19 . Importantly, while well established in human lymphology 40 , water displacement has been shown to yield inaccurate measurements in the mouse-tail model 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies of chronic lymphedema demonstrated that surgery alone did not have a sustained effect on the condition. 21,22 In this study, a hindlimb lymphedema model, in which the iLN together with the associated peripheral lymph vessels and fat tissue were excised, produced acute, but not chronic, edema.…”
Section: Hindlimb Lymphedema Mouse Modelmentioning
confidence: 94%